HUBUNGAN PARTISIPASI USIA LANJUT PADA KEGIATAN POSYANDU LANSIA DENGAN PENGETAHUAN KESEHATAN : POLA HIDUP BERSIH DAN SEHAT - Herry Prasetyo; Petrus Nugroho DS (Kesmas Indonesia, 2009)
The amount of advanced age from year to year tend to increase in Indonesia. It is caused by the result of increasing health service toward advanced age in the health service such the posyandu-advanced age. The knowledge of health such the clean life model and healty would be apparently improved by parcipacing at posyandu-advance age in Bantar village. The aim of this study is to find out the relationship between age participation at posyandu-advanced age with knowledge about health. The study is a quantitative by approaching cross sectional. The total sampling was used and the questionnaires were distribuned to 19 respondents. The chi-square was employed as the data analysis. The finding of this study shows that there is a significant relation between the advanced age participation with the level of knowledge about health where p value 0,000 < 0.005. Therefore, the height of participation has a better knowledge about health. There is about 77,78% of advanced age improved their knowledge of health such, the clean and healthy life model.